2024
DOI: 10.1002/ardp.202300319
|View full text |Cite
|
Sign up to set email alerts
|

Novel quinoline derivatives with broad‐spectrum antiprotozoal activities

Carla B. Hartman,
Phelelisiwe S. Dube,
Lesetja J. Legoabe
et al.

Abstract: Several quinoline derivatives incorporating arylnitro and aminochalcone moieties were synthesized and evaluated in vitro against a broad panel of trypanosomatid protozoan parasites responsible for sleeping sickness (Trypanosoma brucei rhodesiense), nagana (Trypanosoma brucei brucei), Chagas disease (Trypanosoma cruzi), and leishmaniasis (Leishmania infantum). Several of the compounds demonstrated significant antiprotozoal activity. Specifically, compounds 2c, 2d, and 4i displayed submicromolar activity against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Years of scientific research have revealed that chalcones exhibit diverse biological activities ( Rajendran et al, 2022 ; Hartman et al, 2024 ; Yousefian et al, 2024 ), with antioxidant ( Jung et al, 2017 ), antimicrobial ( Zhou et al, 2021 ), anti-inflammatory, antitumor ( Neves et al, 2012 ), anti-infective ( Nowakowska, 2007 ), anticancer ( Binate and Ganbarov, 2023 ), antiviral ( Hu et al, 2023 ), cytotoxic ( Vogel and Heilmann, 2008 ), antiallergic ( Escribano-Ferrer et al, 2019 ), antituberculosis ( Verma et al, 2018 ), and antibacterial ( Nielsen et al, 2005 ; Wang et al, 2023 ; Zhang et al, 2024 ) properties. Chalcones are small, achiral molecules that have molecular weights in the range of 300–600 g/mol and exhibit relatively high lipophilicities ( Nowakowska, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Years of scientific research have revealed that chalcones exhibit diverse biological activities ( Rajendran et al, 2022 ; Hartman et al, 2024 ; Yousefian et al, 2024 ), with antioxidant ( Jung et al, 2017 ), antimicrobial ( Zhou et al, 2021 ), anti-inflammatory, antitumor ( Neves et al, 2012 ), anti-infective ( Nowakowska, 2007 ), anticancer ( Binate and Ganbarov, 2023 ), antiviral ( Hu et al, 2023 ), cytotoxic ( Vogel and Heilmann, 2008 ), antiallergic ( Escribano-Ferrer et al, 2019 ), antituberculosis ( Verma et al, 2018 ), and antibacterial ( Nielsen et al, 2005 ; Wang et al, 2023 ; Zhang et al, 2024 ) properties. Chalcones are small, achiral molecules that have molecular weights in the range of 300–600 g/mol and exhibit relatively high lipophilicities ( Nowakowska, 2007 ).…”
Section: Introductionmentioning
confidence: 99%